2015
DOI: 10.1088/2041-8205/799/2/l25
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic and Dynamical Photospheric Disturbances Observed During an M3.2 Solar Flare

Abstract: This letter reports on a set of full-Stokes spectropolarimetric observations in the near infrared He i 10830Å spectral region covering the pre-, flare, and post-flare phases of an M3.2 class solar flare. The flare originated on 2013 May 17 and belonged to active region NOAA 11748. We detected strong He i 10830Å emission in the flare. The red component of the He i triplet peaks at an intensity ratio to the continuum of about 1.86. During the flare, He i Stokes V is substantially larger and appears reversed comp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
1
7

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 24 publications
3
14
1
7
Order By: Relevance
“…On the other hand, we cannot exclude that the spatial resolution of our observation was insufficient to re-solve the probably very subtle flare-induced velocity changes. Kuckein et al (2015a) reported on newly appearing upflows in response to an M3.2 flare. Although their data were taken with the same instrument, the upflows were stronger next to the PIL rather than along it.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, we cannot exclude that the spatial resolution of our observation was insufficient to re-solve the probably very subtle flare-induced velocity changes. Kuckein et al (2015a) reported on newly appearing upflows in response to an M3.2 flare. Although their data were taken with the same instrument, the upflows were stronger next to the PIL rather than along it.…”
Section: Discussionmentioning
confidence: 99%
“…Rezaei & Beck 2015), sunspots and pores (e.g. Xu et al 2010;Joshi 2014), flares (Judge et al 2014;Kuckein et al 2015), or independently, for example, in small-scale magnetic bright points (Kuckein 2019) or sunspots (e.g. Rezaei et al 2012;Felipe et al 2016;Orozco Suárez et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Spectropolarimetric data of the flare in the Ca II 8542 and He II 10830 Å lines have been analyzed in several works (Penn & Kuhn 1995;Kleint & Judge 2011;Sasso et al 2011;Judge et al 2014Judge et al , 2015Kuckein et al 2015aKuckein et al , 2015b. Using photographic recordings of Stokes I and V profiles in the Ca II H line, Martinez Pillet et al (1990) derived a value of 820(±40)G for B LOS using the weak-field approximation (WFA).…”
Section: Introductionmentioning
confidence: 99%